Pengaruh Penyertaan Modal terhadap Pertumbuhan Aktiva, Efisiensi dan Kinerja Keuangan pada Badan Usaha Milik Daerah (BUMD) (Studi pada BUMD/Perusahaan Daerah di Propinsi Riau) - Sudarno; Idrus, M. Syafi'i; Salim, Ubud; Djumahir (Jurnal Aplikasi Manajemen, 2011)
This research aims to uncover and analyze : (a) whether capital investment could help to improve financial performance, efficiency and has a potential to create the impetus to create asset growth; (b) whether growth of assets could improve the financial performance and create an opportunity to make an efficiency, and (c) whether efficiencies can improve the financial performance of the LGOE of the province of Riau.This study uses quantitative and qualitative methods supported by an open form of questionnaires and interviews. The results of this study, as follows : (1) capital investments have a high power to push financial performance but it has a negative relationship, (2) asset growth has not been capable of improving its financial performance but has a positive relationship, (3) efficiency can improve financial performance but it has a negative relationship, (4) capital investment is potentially to create high efficiency but it has a negative relationship, (5) asset growth does not have great opportunities to improve efficiency and it has a negative relationship, and (6) capital investment does not have the impetus to create asset growth, but it has a negative relationship.